2021
DOI: 10.1063/5.0031120
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of active species in low-pressure capacitively coupled N2/Ar plasmas

Abstract: In this paper, a self-consistent fluid model is developed focusing on the plasma parameters in capacitively coupled 20% N2–80% Ar discharges. Measurements of ion density are performed with the help of a floating double probe, and the emission intensities from Ar(4p) and N2(B) transitions are detected by an optical emission spectroscopy to estimate their relative densities. The consistency between the numerical and experimental results confirms the reliability of the simulation. Then the plasma characteristics,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…We first attributed the observation to our low degree of ionization and an abundance of side reactions enabled by the highly collisional environment at atmospheric pressure. But Liang et al and Bogaerts also found that the production of gas-phase N radicals by the dissociative recombination reactions of N 2 + is insignificant at low pressure and higher electron number density in Ar–N 2 plasma. In our model of an atmospheric pressure Ar–N 2 –H 2 plasma, we found that N 2 + is mostly depleted by collision with H 2 molecules to produce gas-phase N 2 H + rather than neutralization by electrons or charge transfer with Ar, and gas-phase N 2 H + can subsequently play a minor role in consuming NH 3 via the gas-phase reaction N 2 H + + NH 3 → NH 4 + + N 2 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We first attributed the observation to our low degree of ionization and an abundance of side reactions enabled by the highly collisional environment at atmospheric pressure. But Liang et al and Bogaerts also found that the production of gas-phase N radicals by the dissociative recombination reactions of N 2 + is insignificant at low pressure and higher electron number density in Ar–N 2 plasma. In our model of an atmospheric pressure Ar–N 2 –H 2 plasma, we found that N 2 + is mostly depleted by collision with H 2 molecules to produce gas-phase N 2 H + rather than neutralization by electrons or charge transfer with Ar, and gas-phase N 2 H + can subsequently play a minor role in consuming NH 3 via the gas-phase reaction N 2 H + + NH 3 → NH 4 + + N 2 .…”
Section: Discussionmentioning
confidence: 99%
“…The Ar contributing factor never exceeds 1, indicating that electron-impact dissociation of N 2 always dominates. In cases when Ar is the dominant gas component in the plasma, N 2 dissociation by excited Ar has been found to surpass electron-impact dissociation. , Our model predicts that the Ar contributing factor is maximized at E/N = 80 Td, when the mean electron temperature is 2.7 eV, and decreases with high n e .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…产生的离子和中性粒子的温度远小于电子,因此在模型中采用"冷流体"近似, 即假设重粒子的温度为室温(293 K) [14,[23][24][25][26][27][28] ,并在放电过程中保持不变. 此外, 模型中利用所有重物质的质量分数之和为1进行约束,并且假设背景气体为理想 气体.…”
Section: 模型及放电参数unclassified
“…This hybrid model is established based on the framework of multi-physics analysis of plasma sources (MAPS), which is a comprehensive modeling platform developed by Prof. Wang and his group. MAPS consists of various models, such as the global model [39][40][41], fluid model [42][43][44] and PIC/MCC model [45][46][47], which could qualitatively demonstrate physical mechanisms in lowtemperature plasmas. This newly developed hybrid model, which enjoys low computational cost while maintaining great accuracy, makes MAPS more valuable and powerful in quantitative predictions for physical phenomena, as well as in improvement in equipment design.…”
Section: Introductionmentioning
confidence: 99%